Metacognitive training for delusions (MCTd): effectiveness on data-gathering and belief flexibility in a Chinese sample - So, Suzanne Ho-Wai; Chan, Arthur P.; Chong, Catherine Shiu-Yin; Wong, Melissa Hiu-Mei; Lo, William Tak-Lam; Chung, Dicky Wai-Sau; Chan, Sandra S. (Frontiers in Psychology, 2015)
Metacognitive training (MCT) was developed to promote awareness of reasoning biases among patients with schizophrenia. While MCT has been translated into 31 languages, most MCT studies were conducted in Europe, including newer evidence recommending an individualized approach of delivery. As reasoning biases covered in MCT are separable processes and are associated with different symptoms, testing the effect of selected MCT modules would help to develop a targeted and cost-effective intervention for specific symptoms and associated mechanisms. This study tested the efficacy of a 4-session metacognitive training for delusions, MCTd (in Traditional Chinese with cultural adaptations, provided individually), as an adjunct to antipsychotics in reducing severity and conviction of delusions, jumping to conclusions bias and belief inflexibility. Forty-four patients with delusions were randomized into the MCTd or the wait-list control condition. Patients on wait-list received the same MCTd after four weeks of treatment as usual. Assessment interviews took place before and after the treatment, and at 4-week follow-up. There was an additional baseline assessment for the controls. Jumping to conclusions and belief flexibility were measured by the beads tasks and the Maudsley Assessment of Delusions Scale. Attendance rate of the MCTd was satisfactory (84.5%). Compared to treatment as usual, there was a greater reduction in psychotic symptoms, delusional severity and conviction following MCTd. There was a large treatment effect size in improvement in belief flexibility. Improvement in reaction to hypothetical contradiction predicted treatment effect in positive symptoms and delusions. Jumping to conclusions bias was reduced following MCTd, although the treatment effect was not significantly larger than TAU. Our results support the use of process-based interventions that target psychological mechanisms underlying specific psychotic symptoms as adjuncts to more conventional approach